2022
DOI: 10.1007/s40620-021-01193-w
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine monitoring in the follow-up of kidney transplant recipients: consensus indications from an Italian panel of surgeons and nephrologists after the COVID-19 experience

Abstract: The quality of follow-up has clearly emerged as a key factor for long-term kidney graft survival. Currently, many clinics are facing difficulties in delivering optimal surveillance because of the increased number and complexity of kidney transplant recipients, and because of the COVID-19 pandemic. Additional ways of performing follow-up visits are needed and telemedicine has emerged as a tool to strengthen patient care intensity. Six Italian transplant surgeons and nephrologists convened via teleconference to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…An adaptation of the post-renal transplant review visits was made to each stage of the COVID-19 pandemic, marked by the rules dictated by the health authorities and experts' committees [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…An adaptation of the post-renal transplant review visits was made to each stage of the COVID-19 pandemic, marked by the rules dictated by the health authorities and experts' committees [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the fear of contacting COVID-19, we found that ED visits by post-KT patients were not disturbed. A previous study demonstrated that KT recipients had a higher chance of a more severe course of COVID-19 infection than hemodialysis patients[ 18 ]; however, another finding showed that the severity and adverse outcomes were not different between KT recipients and those without for the COVID-19 infection[ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, telemedicine has become one of the most powerful strategies used to follow-up KT recipients[ 18 , 19 ]. Results from Yadav and Singh’s study found that application of telemedicine in the transplant population enhances medication compliance, reduces hospitalization rates, and makes living donor evaluation convenient[ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The initiatives for telemedicine for transplant recipients with COVID-19 are limited to a few publications on a hand full of cases. [55][56][57] In these articles, proof of concept was demonstrated, whereby telemedicine helped assess, diagnose, triage, and treat patients with COVID-19 while avoiding a visit to an emergency department or outpatient clinic. However, large-scale studies have not been published.…”
Section: Impact Of the Coronavirus Disease 2019 Pandemic On Telemedic...mentioning
confidence: 99%